CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, COMPANY VALUE, AND PROFITABILITY AS A MODERATING VARIABLE - Jihan Pratiwi; Arief Rahman; Syafi’i; Muhammad Habibie Al-Hamzah (Jurnal Ekonomi Dan Bisnis, 2025)
This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on company value, while also testing whether profitability can moderate the relationship between CSR variables and company value. This is a descriptive quantitative study, and the population used is the consumer goods industry sector on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The sample in this study was obtained through purposive sampling, resulting in 14 selected companies based on pre-determined criteria. The analysis methods used were multiple linear regression and Moderated Regression Analysis (MRA), with classical assumption tests as prerequisites. In this study, the CSR variable was measured using the GRI Standards 2021, company value using Tobin’s Q, and profitability measured by ROA. The results of the study indicate that CSR has a negative and significant effect on company value, suggesting that CSR activities are not yet fully appreciated by the market as value creators. Additionally, the MRA results show that profitability is unable to moderate the relationship between CSR and company value. This finding indicates that even though companies generate profits, this is insufficient to strengthen the influence of CSR on company market value.